The Role of Internal Audit in Mitigating Operational Risks in Sharia Banks - Utami, Rizky Ananda; Irsyad, Fairuz Azzahra; Siregar, Saparuddin (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
The role of internal audit in Islamic banks is very important to mitigate operational risks, which must be managed specifically to comply with sharia principles. Operational risks in Islamic banks include challenges such as human error, system failures, and external risks, which can have a serious impact on the stability and reputation of the bank. This study aims to analyze the role of internal audit in supporting operational risk management in Islamic banks, as well as identify strategic measures to improve its effectiveness. The methodology used involves thematic analysis of relevant literature studies, which highlight that while internal audit plays an important role in maintaining compliance and improving corporate governance, there are barriers to the implementation of proactive risk management. This study finds that the integration of internal audit with Good Corporate Governance (GCG) principles and the use of technologies such as blockchain are important steps to strengthen supervision and increase transparency in mitigating operational risks. The results of this study are expected to be a reference to strengthen the stability and competitiveness of Islamic banks in facing operational risk challenges in the banking industry.